DURABLITIY STUDY OF CONCRETE USING NANOSILICA AND RICE HUSK ASH (International Journal of Engineering Management Science, 2018)
The durability of concrete structures plays a significant role in modern construction,especially in aggressive environments. This work discus ses the impact of nano-silica(NS) and rice husk ash (RHA) substitution as a partial cement replacement in concretein order to improve the durability of concrete. This paper discusses the supplementarycementitious materials (SCMs) together with their synergy concerning mechanicalproperties, sulfate resistance, chloride ion penetration, water absorption, andcarbonation depth. Experimental studies were conducted based on the ASTMstandards for consistency and reliability. Incorporation of NS and RHA improves thepozzolanic reaction, resulting in a finer microstructure and reduced permeability, thusimproving the durability of concrete. Significant improvements in the strength anddurability characteristics have been seen compared with the conventional concrete.This work sheds light on sustainable construction by utilizing industrial by-productsand helps in the reduction of cement consumption, hence, lowering environmentalimpacts. The result reveals that the durability of NS and RHA could enhance concreteservice life for the structure.